Effects of artificial substrate and night-time aeration on the water quality in Macrobrachium amazonicum (Heller 1862) pond culture - Henares, Matheus Nicolino Peixoto; De Lima Preto, Bruno; Rosa, Fabricio Ribeiro Tito; Valenti, Wagner Cotroni [UNESP]; Camargo, Antonio Fernando Monteiro (Hindawi, 2013)
The effects of artificial substrate and night-time aeration on the culture of Macrobrachium amazonicum were evaluated in 12 ponds stocked with 45 prawns m-2. A completely randomized design in 2 × 2 factorial scheme with three replicates was used. The combination of factors resulted in four treatments: with substrate and aeration (SA), with substrate and without aeration (SWA), without substrate and with aeration (WSA) and without substrate and aeration (WSWA). The presence of substrate in SA and SWA treatments reduced suspended particles (seston) by ~17.3% and P-orthophosphate by ~50%. The use of aerator (WSA and SA treatments) significantly (P < 0.05) increased the concentration of dissolved oxygen, suspended particles and nutrients in the pond water. These results indicate that the effect of substrate on turbidity and total suspended solids (TSS) values is opposite to the effect of the aerator. The aerators in semi-intensive grow-out M. amazonicum farming lower water quality because they increased the amount of detritus and nutrients in the pond water. On the other hand, the use of artificial substrate reduces turbidity values, chlorophyll a, TSS and P-orthophosphate concentrations. Therefore, the combination of substrate addition and night-time aeration is not interesting because they have opposite effects. © 2013 John Wiley & Sons Ltd.
Keywords: Crustacean; Freshwater prawn; Limnology; Nitrogen; Phosphorus